Railways in Development : Global Round-Up 1996-2005 - Amos, Paul (World Bank, Washington, DC, 2012)
This Transport Note has been prepared as an adjunct to the 2006-07 updating of the World Bank's Railways Databases. It uses the databases for inferences on aggregate trends as well as other Bank documents and sources of policy information. It provides a high level view of traffic and policy developments. Particular emphasis is given to the Bank's six regions of operations at a time when the Bank's Transport Strategy is being updated with the intention of increasing the attention given to the role of railways in development. For completeness, important policy developments in the higher income countries are also summarized. The Note has been prepared by Paul Amos, Transport Adviser to the World Bank and Lou Thompson, Railway Consultant, and formerly Railways Adviser to the World Bank. While the content has drawn upon the broad experience and expertise of the Bank in the railway sector, any views expressed herein are strictly those of the authors.